Aliskiren – a promising strategy for ovarian ischemia/reperfusion injury protection in rats via RAAS. (2nd August 2016) - Bayir, Yasin; Cadirci, Elif; Polat, Beyzagul; Kilic Baygutalp, Nurcan; Albayrak, Abdulmecit; Karakus, Emre; Un, Harun; Keles, Mevlut Sait; Kocak Ozgeris, Fatma Betul; Toktay, Erdem; Karaca, Mehmet; Halici, Zekai
Abstract: The aim of this study was to evaluate the effects of aliskiren, direct renin inhibitor, as an antioxidant and tissue protective agent and evaluate the molecular, biochemical, and histopathological changes in experimental ischemia and ischemia/reperfusion injury in rat ovaries. Forty-eight female rats were randomly divided into eight groups: in Group 1, only sham operation was performed. Group 2 received 100 mg/kg aliskiren and sham operated. In Group 3, 3 h-period of bilateral ovarian ischemia was applied. Group 4 received a 3-h period of ischemia followed by 3 h of reperfusion. Groups 5 and 6 received 50 and 100 mg/kg, respectively, of aliskiren and bilateral ovarian ischemia was applied (after a 3-h period of ischemia, both ovaries were surgically removed). To Groups 7 and 8, 50 and 100 mg/kg of aliskiren were administered, respectively, and the induction of ischemia was performed. At the end of a 3-h period of ischemia, bilateral vascular clips were removed, and 3 h of reperfusion continued. After the experiments, IL-1β, IL-6, TNF-α, and iNOS mRNA expressions and SOD, GSH, MDA, renin, and angiotensin-II levels were determined and histopathological changes were examined in rat ovaries. Aliskiren treatment normalized excessive changes in cytokine and oxidative stress markers in both ischemia and ischemia/reperfusion injury. Histopathologically, treatment with aliskiren ameliorated the development of ischemia and/or ischemia/reperfusion tissue injury. This study concluded that aliskiren treatment is effective in reversing ischemia and/or ischemia/reperfusion induced ovary damage via the improvement of oxidative stress, reduction of inflammation, and suppression of the renin-angiotensin aldosterone system.